Systemic Functional Approach in English Grammar as a Foreing Language. / Enfoque sistémico funcional de la gramática del inglés como lengua extranjera. - HARTHATY, INDRIE (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT It used to be confusing for english as a foreign language (EFL) learners to understand the meanings of past participle functioning as modifiers. The data was taken from workbook entitled english for secretaries and administrative personnel written by MariselaToselli and Ana Maria Milan. This study results that past participle is labelled as a classifier when it precedes the thing, whereas the past participle is labelled as a qualifier when it follows the thing. Past participle functioning as a classifier expresses restriction. Past participle as a qualifier characterizes or provides additional information about the thing. RESUMEN Solía ser confuso para los estudiantes de inglés como lengua extranjera (ILE) entender los significados del participio pasado funcionando como modificadores. Los datos se tomaron del libro de trabajo titulado Inglés para secretarias y personal administrativo escrito por Marisela Toselli y Ana Maria Milan. El resultado de este estudio es que el participio pasado se etiqueta como clasificador cuando precede a la cosa, mientras que el participio pasado se etiqueta como calificador cuando sigue a la cosa. El participio pasado que funciona como clasificador expresa restricción. El participio pasado como calificador caracteriza o proporciona información adicional sobre la cosa.